The impact of verbal working memory on written translation: Empirical evidence and an initial model - Li, Jie (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Working memory refers to a metaphorical mental workspace involved in the temporary storage and processing of information which has been considered a key construct in Cognitive Translation Studies. This study investigates whether verbal working memory in the translator’s first and/or second language is related to written translation speed and quality. Through three selection tests, 33 student translators in the second or third year of their Master’s in Translation and Interpreting at nine Chinese universities were selected to participate. In the first test, processing and storage capacities of verbal working memory in their first and second language were assessed separately by means of a dual-task paradigm implemented in the e-Prime software suite. In the second study, participants translated a technical text from their second language to their first language. Their behavioural data were collected with a keylogger and the quality of their translations was evaluated by four expert translators. The correlation analysis suggests that the processing function of verbal working memory in the second language does affect logged translation speed; and that the processing function of verbal working memory in the first language has an effect on translation quality. Furthermore, through regression analysis, an initial model was established, which shows the precise structure of the impact of bilingual working memory on written translation. These findings have significant implications for translation skills training. It appears that additional verbal working memory training for both first and second languages would enhance the students’ translation skills.